(3TQM GdeaGJjMs - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s
(3ChdgG (B:s
(3cJGH GdWgGQI Cj gPG cJGH GdWgGQI hGdcJGH GSe eaQO LeYg cJH HVe GdJGA hSchfgG(B...s
(3BNQgG (B:s
(3eHJhQ GdBNQ hBNQ GdehLhO efg bhdg(B: ...(3fXQ Edi Cf GdZGdH YOe GdGfaUGd Hjf GdJecf ef GdZSd aj GHJOGA GdJjee hHYO GdaQGZ efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B279s
(3GdPQjYI(B:(3L(B14(3,U(B48(3,JMJ Qbe (B1811s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis